American grown : the story of the White House kitchen garden and gardens across America - Obama, Michelle, 1964- (Random House, 2012)
A sumptuously photographed guide by the first lady describes how her daughters and she planted a vegetable garden on the White House's South Lawn as part of an initiative to raise awareness about childhood obesity, in a reference that shares gardening tips, recipes and advice for making healthier food choices.